2018
DOI: 10.4103/jcd.jcd_52_18
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric evaluation of white spot lesion treatment using novel resin infiltration material (ICON®)

Abstract: Aims and Objectives:The aim of this study is to compare the esthetic improvement of white spot lesions (WSLs) treated by icon, sodium fluoride (NaF), and bioactive glass using VITA Easyshade® spectrophotometer.Methodology:Ninety intact human maxillary central incisors were collected and artificial WSLs were created on facial surface having dimensions of 4 mm × 4 mm by immersing in demineralized solution for 4 days, baseline comparisons were performed by measuring the color of the WSLs compared to the adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Aesthetics is an important aspect of modern dentistry, and infiltration allows for minimally interventional treatment of lesions while maintaining the continuity of the patient’s own tissues, which definitely has a positive effect on the final result in terms of aesthetics of the treated area. Studies available in the literature have shown that not only Icon infiltrant, but also the composite sealers Opiguard (Kerr, Orange, CA, USA) and PermaSeal (Ultradent, South Jordan, UT, USA) applied on the surface of early carious lesions proved to be able to infiltrate and, moreover, showed similar improvements in terms of aesthetics, and the colour stability of the infiltrated white spots lasted for at least 2 months [ 26 , 27 ]. That issue was also addressed by Paris et al and Yuan et al, who found that colour change and masking of early carious lesions can be achieved with use of infiltrants whose RI (refractive index) is close to that of enamel [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aesthetics is an important aspect of modern dentistry, and infiltration allows for minimally interventional treatment of lesions while maintaining the continuity of the patient’s own tissues, which definitely has a positive effect on the final result in terms of aesthetics of the treated area. Studies available in the literature have shown that not only Icon infiltrant, but also the composite sealers Opiguard (Kerr, Orange, CA, USA) and PermaSeal (Ultradent, South Jordan, UT, USA) applied on the surface of early carious lesions proved to be able to infiltrate and, moreover, showed similar improvements in terms of aesthetics, and the colour stability of the infiltrated white spots lasted for at least 2 months [ 26 , 27 ]. That issue was also addressed by Paris et al and Yuan et al, who found that colour change and masking of early carious lesions can be achieved with use of infiltrants whose RI (refractive index) is close to that of enamel [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…One major goal of preventive dentistry is to stop the progression of incipient carious lesions and induce their remineralization. This is done to prevent the extension of carious lesions and preserve the tooth structure (19).…”
Section: Discussionmentioning
confidence: 99%
“…The cariogenic solution had a pH of 4 and contained 0.5 g yeast extract, 1 g glucose, and 2 g sucrose. Several studies show that such a procedure using artificial cariogenic solutions can simulate WSLs as they form in the oral environment (19,20). The formed biofilm was wiped off by a wet gauze and the nail varnish was removed with a scalpel.…”
Section: Methodsmentioning
confidence: 99%
“…Resin infiltration stopped enamel demineralization and corrected the appearance of white-spot lesions. [11][12][13] This procedure seems to be microinvasive; therefore, it could act as a bridge between noninvasive and minimally invasive procedures for treating initial carious lesions. 14 The goal of this approach is to use resin monomer to infill the intercrystalline micropores inside the lesion body.…”
Section: Introductionmentioning
confidence: 99%